2020
DOI: 10.1177/1076029620982669
|View full text |Cite
|
Sign up to set email alerts
|

Deep Venous Thrombosis in COVID-19 Patients: A Cohort Analysis

Abstract: Deep venous thrombosis (DVT) is a severe complication of coronavirus disease 2019 (COVID-19). The purpose of this study was to study the prevalence, risk factors, anticoagulant therapy and sex differences of DVT in patients with COVID-19. The enrolled 121 hospitalized non-ventilator patients were confirmed positive for COVID-19. All suspected patients received color Doppler ultrasound (US) to screen for DVT in both lower extremities. Multivariate logistic regression was performed to identify risk factors relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 26 publications
5
27
1
2
Order By: Relevance
“…The female-only group also demonstrated a relative increase in extremity duplex exams, 5.3% of the study population in 2019 compared to 8.3% in 2020. Thromboembolism is an established complication of COVID-19 [24,25] so an increase in the percentage of these examinations performed would be an expected finding. In the pandemic cohort, there were 57 extremity duplex exams performed and 8 of these studies demonstrated venous thromboses.…”
Section: Discussionmentioning
confidence: 97%
“…The female-only group also demonstrated a relative increase in extremity duplex exams, 5.3% of the study population in 2019 compared to 8.3% in 2020. Thromboembolism is an established complication of COVID-19 [24,25] so an increase in the percentage of these examinations performed would be an expected finding. In the pandemic cohort, there were 57 extremity duplex exams performed and 8 of these studies demonstrated venous thromboses.…”
Section: Discussionmentioning
confidence: 97%
“… 44 Coincidentally, initial elevated levels of D-dimer in baseline diminished after anticoagulant therapy with LMWH in DVT-COVID-19 patients and continuously higher than non-DVT-COVID-19 patients, indicating changes of D-dimer present an improvement in hypercoagulable state as well as a stable biomarker for anticoagulant effect in COVID-19 therapy. 45 Recently, researchers found D-dimer levels could affect anticoagulant doses. Prophylactic dose of heparin has been revealed its efficacy and better prognosis among users with D-dimer >6 times the upper limit of normal value (ULN) by improving 28-day mortality than that of nonusers (32.8 vs 52.4%) while users with D-dimer ≤1 ULN of no benefit.…”
Section: Discussionmentioning
confidence: 99%
“…The miRNA-320 family has already been described in patients with deep vein thrombosis (DVT) [ 25 , 26 ]. DVT is also a severe complication of COVID-19 patients and, therefore, the identification of high-risk COVID-19 patients is important to promptly initiate thrombosis prophylaxis [ 27 ]. In contrast to our findings, Jiang et al reported a significant up-regulation of miRNA-320a and miRNA-320b correlating with D-dimer concentrations in DVT patients, but not in post-thrombotic syndrome [ 25 ].…”
Section: Discussionmentioning
confidence: 99%